Evaluasi Penatalaksanaan Abortus Inkompletus Di Rumah Sakit Y: Studi Retrospektif - Rabuana, Susi; Suardi, Yunita Suriani (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Incomplete abortion is a common first-trimester pregnancy complication encountered in obstetric emergency departments and requires immediate treatment to prevent maternal morbidity and mortality. Inappropriate management can increase the risk of infection, severe bleeding, and even future fertility problems. This community service activity aims to evaluate the management of incomplete abortion at Hospital Y through a retrospective study of patient medical records over the past five years (2019–2023). The methods used included secondary data collection from the medical records of patients with incomplete abortion, descriptive analysis of the types of medical procedures provided, treatment time, complications, and compliance with hospital standard operating procedures (SOPs) and WHO guidelines. The evaluation results showed that 85% of management met standards, with curettage (63%) the most common procedure, followed by misoprostol administration and observation. The main obstacles identified were delays in treatment for referred patients and insufficient documentation on patient education sheets. This activity provided important input for hospitals to improve service quality, such as retraining healthcare workers, enhancing medical information systems, and strengthening referrals between facilities. It is hoped that this evaluation can inform policy improvements to the management of incomplete abortion cases at the hospital and regional levels.